The State-of-Art of Tourism Planning in Archipelagic Philippines 2001-2010: A Case Review - Virgilio M. Maguigad (Centre For Tourism Planning and Development, 2012)
Tourism is a development option that is pursued by the Philippines from the 1970s until present where it is a pillar of the country's economy. Arrivals from foreign origins are increasing at double digit growth rates while domestic tourism continues to outpace international arrivals. Recent legislation on tourism during the past two years has continued to place importance on the industry as an engine of growth. However, such legislation should be viewed against the backdrop of local governance structures that includes processes on comprehensive land and water use planning. The country faces a lack of environmental planners (as urban and regional planners are formally called in the Philippines) where tourism planning is a sub-specialization. This paper describes and reviews the current state-of-art of tourism planning in the Philippines against this backdrop of governance, the planning profession and tourism legislation.